The impact of charter schools on student academic achievement - Mark P. Gius (Journal of Business and Economic Studies (JBES), 2021)
The purpose of the present study is to examine the impact of charter schools on student academic achievement. Using school level data from Massachusetts for the period 2011-2017, it was found that charter schools had higher average SAT scores in both math and reading than non-charter public schools, holding all other factors constant. Using a random effects model, it was found that the average math SAT score was 17.6 points higher in charter schools, and the average reading SAT score was 28.6 points higher in charter schools. These results corroborate the findings of prior studies, especially Angrist, Cohodes, Dynarski, Pathak, and Walters (2016).
Keywords: 330; Charter School; Academic Achievement; SAT Scores